Domestic violence in Medellín and other municipalities of Aburrá Valley 2003-2004 - Nilton E. Montoya; Luis F. Duque (Universidad de Antioquia, 2008)
Objective: To estimate the magnitude and distribution by sex of domestic or family violence (between partners, siblings, and from parents to children) in Medellin, Colombia and nine surrounding municipalities (Medellin metropolitan area), 2003-2004. Methods: Household survey to a representative multistage sample to non institutionalized population, within 12 and 60 years of age, in the urban area of each municipality. Results: Verbal or psychological aggression and victimization: 64% and 61%, physical violence without physical injury: 17% and 14%, physical violence with physical injury: 2% and 3% between intimate partners. Intimate partners' aggression and victimization do no differentiate by sex. Verbal, psychological and physical aggression from parents toward children is 60%, and physical aggression with physical injury is near 10%. 55% of families reported fights among siblings, and 3% with physical injury. Medellin has the highest rates of family or domestic violence compared with the other municipalities of Aburra Valley. Domestic violence charge is very low (5-20%), and masculine victims rather prefer not to report. Conclusions: We suggest not to ground public policies on current statistics, but to establish a system of periodic surveys, representative of general population or families. It seems important to have two different types of interventions: domestic or family violence prevention considering family as a unit that interacts with the surrounding; and rehabilitation of chronic and severe domestic aggressors.